Development of a Patient Preference Survey for Wearable Kidney Replacement Therapy Devices. Issue 7 (28th July 2022) - Flythe, Jennifer E.; Forfang, Derek; Gedney, Nieltje; White, David M.; Wilkie, Caroline; Cavanaugh, Kerri L.; Harris, Raymond C.; Unruh, Mark; Squillaci, Grace; West, Melissa; Mansfield, Carol; Soloe, Cindy S.; et al.
Key Points: We included the risks of serious bleeding and serious infection based on patient concerns and regulator input about future trial end points. The survey will estimate maximal acceptable risks for serious bleeding and infection and willingness to wait for devices with lower risk. Visual Abstract: Abstract : Background: Recent innovations have the potential to disrupt the current paradigm for kidney failure treatment. The US Food and Drug Administration is committed to incorporating valid scientific evidence about how patients weigh the benefits and risks of new devices into their decision making, but to date, premarket submission of patient preference information (PPI) has been limited for kidney devices. With input from stakeholders, we developed a survey intended to yield valid PPI, capturing how patients trade off the potential benefits and risks of wearable dialysis devices and in-center hemodialysis. Methods: We conducted concept elicitation interviews with individuals receiving dialysis to inform instrument content. After instrument drafting, we conducted two rounds of pretest interviews to evaluate survey face validity, comprehensibility, and perceived relevance. We pilot tested the survey with in-center hemodialysis patients to assess comprehensibility and usability further. Throughout, we used participant input to guide survey refinements. Results: Thirty-six individuals receiving in-center or home dialysis participated in concept elicitation ( N =20) and pretest ( N =16) interviews. Participants identified reduced fatigue, lower treatment burden, and enhanced freedom as important benefits of a wearable device, and many expressed concerns about risks related to device disconnection—specifically bleeding and infection. We drafted a survey that included descriptions of the risks of serious bleeding and serious infection and an assessment of respondent willingness to wait for a safer device. Input from pretest interviewees led to various instrument modifications, including treatment descriptions, item wording, and risk-level explanations. Pilot testing of the updated survey among 24 in-center hemodialysis patients demonstrated acceptable survey comprehensibility and usability, although 50% of patients required some assistance. Conclusions: The final survey is a 54-item web-based instrument that will yield estimates of the maximal acceptable risk for the described wearable device and willingness to wait for wearable devices with lower risk.